-
The analytic expression of two circles, their intersection is the solution.
-
1+4λ)x+6y=0…①;6x+(2+λ)y=0…②;4x∧2+y∧2=25…③;Derived from the formula, y [ 1 4 ) 6]x [ 6 (2 )x; 1 4 ) 6 6 (2) Simplification ( 2) (4 17) 0;λ1=2;λ2=-17/4;Substituting 1 2 into the formula, 9x 6y 0, y 3x 2...., substituting the formula into , 4x 2 (9 4) x 2 25, simplifying, x 2 4, x1 2, x2 2, substituting x1 2 into the formula, getting y1 3, substituting x2 2 into the formula, getting y2 3;Substituting 2 17 4 into the formula, we get, 16x 6y 0, y 8x 3...., substituting the formula into , 4x 2 (64 9) x 2 25, simplifying, x 2 9 4, x3 3 2, x4 3 2, substituting x3 3 2 into the formula, getting y3 4, substituting x4 3 2 into the formula, getting y4 4. It's not easy to type on your phone, hope, if you have any questions, please ask.
Can it solve your problem?
-
x-y=0......(1)
5x-7y-2=0......Silver (2).
Solution: Use the method of addition and subtraction to prepare for the elimination of the element.
1) 7 A (2) gets:
2x+2=0
x = a 1 from (1) gets:
y=x=a1
So the solution of the original equation is ruined: =y=a1.
-
x-y=4 4x+2y=-1 is substituted by x=4+y, and 4(4+y)+2y=-1 is solved to get y= -17 6 x=4+(-17 imitation 6)=7 6
-
x+y=5 (1)
2x-y=4 (2)
1) +(2) to get:
3x=5+4
x=9 3x=3 is substituted into the original equation (1) to obtain:
y=5-3=2
-
Commutation method, 2x y 4 = 0
y= 2x-4
Bring in x +y 2x 4y=0 to get x +(2x 4)( 2x 4) 2x 4(2x 4)=0
Find 5x -26x+32=0
x1= x2=2
y1= y2=0
-
+ is x+y=6
That's x-y=20
Will it be done after that!?
-
x=(3y+4)/2
y=(2x-4)/3
x-3y=t 2x+y=t
then x-3y=2x+y
radius in mm. 2850 square millimeters = square centimeters.
A: The total area is in square centimeters.
-
Is the bracket misplaced?
-
From 4x 2-y 2=0 can be decomposed into (2x+y)(2x-y)=0, find y=-2x, y=2x, and substitute them into x 2-xy+4=0 respectively in 3x 2+4=0, of course, this formula has no solution; If y=2x, then there is -x 2+4=0, find x=+2 or -2
-
4x -y = (2x+y)*(2x-y)=0 to get 2x=-y or 2x=y; Substituting 2x=-y into x -xy+4=0 gives 3x =-4, which is not true; Substituting 2x=y into x -xy+4=0 gives x =4 to get x=2 or -2, so x=2, y=4 or x=-2, y=-4
-
By 4x 2-y 2 = 0 y = 2x
From x 2-xy+4=0, we know y≠-2x
Then, x 2-2x 2+4=0, x=2 or -2 are solved as x=2, y=4
or x=-2 y=-4
-
3x+4y=5 1 formula.
7x+9y=-5 2 2 formula.
Multiply 1 by 7 to get: 21x+28y=35 3x2 multiply by 3 to get: -21x+27y=-15 2 4 3+4 get: 55y=55 2
y=1 2, substitute y=1 2 into 3x+4y=5
x=1so.
x=1y=1/2
-
This is the score, 2 at the bottom and 5 at the top.
-
1+2; -4x+13y=0, get x=(13 4)y and bring in 1 to solve it.
2x+2y=1 ①
6x-6y=1 ② >>>More
5/x+6/y=8(1)
1/x-3/y=-11(2) >>>More
2x+my-2x-8y=4-16
8-m)y=12 >>>More
Let the original grass on each acre of land be A, the grass growing every week is B, and the grass eaten by each cow per week is C, then: the total amount of grass on 2 acres of land eaten by 3 cows in 2 weeks is 2A+2*2B=2A+4B; Grass eaten per cow per week (a+2b) 3. >>>More
Solution: Because x=3, y=-2
Substitute ax+by=1 >>>More